Education for students with disabilities – Polish and Hungarian solutions - Czerwińska, Kornelia; Konieczna, Iwona; Beáta Prónay, Beáta Prónay (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The article is a direct outcome of a discourse aimed at exchanging experiences and views in the area of education and rehabilitation for people with disabilities in Poland and Hungary, undertaken as part of scientific cooperation between universities which deal with the issues of special education among others. The authors attempt to perform and present a comparative analysis of current academic solutions for students with disabilities in both countries. Similarities and differences in the solutions discussed, especially problematic areas currently showing in the educational systems, constitute the basis for further discussion and research aimed at developing best practices that would ensure quality education for children and adolescents with disabilities.